The economics of money, banking, and financial markets - Mishkin, Fredrick S. (Massachusetts Addison-Wesley, 1998)
This edition has many insights on the monetary policy process, the regulation and supervision of the financial system, and the internationalization of financial markets.
Includes bibliographic reference, index
osc 26/5/17
Loans
Keywords: Monetary Economics; Financial market; Banks and banking; Money; Finance